PENGARUH KUALITAS LAYANAN DAN CITRA LEMBAGA TERHADAP KEPUASAN SERTA DAMPAKNYA PADA PEMBERIAN REKOMENDASI KEPADA ORANG LAIN (STUDI PADA TARUNA STIMART “AMNI” SEMARANG) (Students' Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of service quality and the institution image to the satisfaction, and examine the effect of service quality, the image of the institution, satisfaction to recommend to others. This research is a quantitative research conducted in educational institutions of Stimart Amni Semarang majoring of Teknika, Nautical and management. Samples were obtained by random sampling and obtained as many as 130 students. Data collection was conducted by spreading questionnaires to the respondents. The questionnaire was contained the closed questions with five alternative answers including strongly disagree, disagree, neutral, agree and strongly agree. Data analysis was using linear regression test. The results showed that the service quality has positive influence and significant on satisfaction, the institution image has positive influence and significant on satisfaction, service quality has positive influence and significant on recommendation to the others, the institution image has positive influence and significant on recommendation to the others, and satisfaction has positive influence and significant on recommendation to the others. Keywords : service quality, the institution image, satisfaction and recommendation